DAMPAK APLIKASI PLATFORM MERDEKA MENGAJAR (PMM) TERHADAP KINERJA GURU TIK DI SMP NEGERI 7 KOTA CILEGON - Ismatullah; Popi Dayurni; Anisa Hermalistiawati (STKIP Subang, 2025)
This study aims to evaluate the impact of using the Merdeka Mengajar Platform (PMM) on the performance of ICT teachers at SMP Negeri 7 in Cilegon City. This application has become an important means in implementing the Merdeka Curriculum to improve the quality of teaching. Using a qualitative method and a case study approach, this research reveals various benefits as well as challenges faced by teachers in utilizing PMM. The results indicate that PMM assists teachers in designing more effective learning, although there are obstacles such as technological skills and internet access. This study recommends intensive training and infrastructure improvement to optimally support the utilization of PMM.